Trophic activity of human P2X7 receptor isoforms A and B in osteosarcoma. - Anna Lisa Giuliani; Davide Colognesi; Tiziana Ricco; Carlotta Roncato; Marina Capece; Francesca Amoroso; Qi Guang Wang; Elena De Marchi; Allison Gartland; Francesco Di Virgilio; Elena Adinolfi (PLoS ONE)
The P2X7 receptor (P2X7R) is attracting increasing attention for its involvement in cancer. Several recent studies have shown a crucial role of P2X7R in tumour cell growth, angiogenesis and invasiveness. In this study, we investigated the role of the two known human P2X7R functional splice variants, the full length P2X7RA and the truncated P2X7RB, in osteosarcoma cell growth. Immunohistochemical analysis of a tissue array of human osteosarcomas showed that forty-four, of a total fifty-four tumours (81.4%), stained positive for both P2X7RA and B, thirty-one (57.4%) were positive using an anti-P2X7RA antibody, whereas fifteen of the total number (27.7%) expressed only P2X7RB. P2X7RB positive tumours showed increased cell density, at the expense of extracellular matrix. The human osteosarcoma cell line Te85, which lacks endogenous P2X7R expression, was stably transfected with either P2X7RA, P2X7RB, or both. Receptor expression was a powerful stimulus for cell growth, the most efficient growth-promoting isoform being P2X7RB alone. Growth stimulation was matched by increased Ca(2+) mobilization and enhanced NFATc1 activity. Te85 P2X7RA+B cells presented pore formation as well as spontaneous extracellular ATP release. The ATP release was sustained in all clones by P2X7R agonist (BzATP) and reduced following P2X7R antagonist (A740003) application. BzATP also increased cell growth and activated NFATc1 levels. On the other hand cyclosporin A (CSA) affected both NFATc1 activation and cell growth, definitively linking P2X7R stimulation to NFATc1 and cell proliferation. All transfected clones also showed reduced RANK-L expression, and an overall decreased RANK-L/OPG ratio. Mineralization was increased in Te85 P2X7RA+B cells while it was significantly diminished in Te85 P2X7RB clones, in agreement with immunohistochemical results. In summary, our data show that the majority of human osteosarcomas express P2X7RA and B and suggest that expression of either isoform is differently coupled to cell growth or activity.